Informed consent: a post-operative assessment - Kruger, Roger (University of the Free State, 2011)
English: The researcher’s observation that patients do not always understand what they are consenting to was confirmed by various sources. According to Northouse and Northouse (1998: 270) and the South African Department of Health (2006: 11) patients’ lack of comprehension in the process of informed consent is a general phenomenon taking place in every hospital setting due to factors such as lack of interpersonal relationships between the health care professional and the patient cultural practices as well as language. A quantitative, descriptive study design was used to describe the process of obtaining informed consent prior to a surgical procedure in a hospital in the Northern Cape. Specific objectives were to: (1) describe the current practice of obtaining informed consent prior to a surgical procedure or an operation; and (2) make recommendations to relevant stakeholders for the purpose of improving the process of informed consent for an operation or procedure and thus the quality of health care. A structured interview, based on a questionnaire, was used to gather information using convenient sampling as the primary sampling method because it was feasible and affordable. A pretest was done before the main data collection process, but the results were not included in the final results. Data collection took place over a period of 90 days and included 150 participants who all met the inclusion criteria determined by the researcher. The researcher was assisted by a biostatistician who made use of Statistical Analyses Software (SAS) in order to analyze the data. Descriptive statistics namely means and standard deviations or medians and percentiles were calculated for continuous data. Frequencies and percentages were calculated for categorical data, and the analysis was done by a biostatistician. The researcher organized the study results according to tenets of capacity to consent to give meaning to the data and make it easy to understand. Figures and tables were used to present the large amount of detailed information concisely and clearly. More than one third of the sample was vulnerable due to their low educational level and unawareness of their rights as patients. Unfortunately no effort was made to ensure that they fully comprehended what they were consenting to. Recommendations focused on strategies to improve understanding by patients and to inform patients of their rights and responsibilities.

Afrikaans: Die observasie van die navorser dat pasiënte nie altyd verstaan waarvoor hul toestemming gee nie, was bevestig deur verskeie bronne. Volgens Northouse en Northouse (1998: 270) en die Suid-Afrikaanse Departement van Gesondheid (2006: 11) is pasiënte se gebrek aan begrip tydens die proses van ingeligte toestemming ‘n algemene verskynsel wat plaasvind in elke hospitaal opset as gevolg van faktore soos gebrek aan interpersoonlike verhoudinge tussen die gesondheidssorgpraktisyn en die pasiënt se kulturele praktyke asook tale. ‘n Kwantitatiewe, beskrywende studie ontwerp was gebruik om die verkrygingsproses van ingeligte toestemming voor ‘n chirurgiese prosedure in ‘n hospitaal in die Noordkaap te beskryf. Spesifieke objektiewe was om: (1) die huidige verkrygingspraktyk van ingeligte toestemming voor ‘n chirurgiese prosedure of operasie te beskryf; en (2) aanbevelings te maak aan relevante aandeelhouers om die proses van ingeligte toestemming vir ‘n operasie of prosedure te verbeter, en dus die kwaliteit van gesondheid. ‘n Gestruktureerde onderhoud gebaseer op ‘n vraelys was gebruik om inligting in te samel, deur die gebruik van die gemaklikheidstoetsing as die primêre toetsingsmetode omdat dit uitvoerbaar en bekostigbaar was. ‘n Voorondersoek was voor die hoof data-insamelingsproses gedoen, maar die uitslae was nie by die finale resultate ingesluit nie. Data-insameling het plaasgevind oor ‘n periode van 90 dae en het 150 deelnemers ingesluit wat almal die insluitingskriteria bereik het, wat deur die navorser bepaal is. Die navorser was bygestaan deur ‘n biostatistikus wie gebruik gemaak het van Statistiese Analise Sagteware (SAS) om die data te ontleed. Beskrywende statistieke naamlik middeletoetse en standaard afwykings of mediane en persentuele was bereken vir ononderbroke data. Frekwensies en persentasies was bereken vir kategoriese data. Die analise was gedoen deur die biostatistikus. Die navorser het die studie resultate volgens beginsels van kapasiteit om toestemming georganiseer, om betekenis aan die data te lewer en dit verstaanbaar te maak. Figure en tabelle was gebruik om die groot hoeveelheid gedetailleerde inligting bondig en duidelik te presenteer. Meer as een derde van die steekproef was kwesbaar as gevolg van hul lae onderrigvlak en onbewustheid van hul regte as pasiënte. Ongelukkig was geen poging aangewend om te verseker dat hul verstaan waarvoor hul toestemming verleen nie. Aanbevelings het gefokus op strategieë wat pasiënt verstandhouding verbeter en om hul in te lig van hul regte en verantwoordelikhede.
Keywords: Dissertation (M.Soc.Sc. (School of Nursing)) -- University of the Free State, 2011; Informed consent (Medical law) -- South Africa; Patient participation -- South Africa; Hospital patients -- Legal status, laws, etc.; Medical ethics; Physician and patient; Hospital patients -- Intelligence levels -- South Africa; Patient education